Local auxin synthesis mediated by YUCCA4 induced during root-knot nematode infection positively regulates gall growth and nematode development - Suzuki, Reira; Kanno, Yuri; Abril-Urias, Patricia; Seo, Mitsunori; Escobar, Carolina; Tsai, Allen Yi-Lun; Sawa, Shinichiro (Frontiers in Plant Science, 2022)
Parasites and pathogens are known to manipulate the host’s endogenous signaling pathways to facilitate the infection process. In particular, plant-parasitic root-knot nematodes (RKN) are known to elicit auxin response at the infection sites, to aid the development of root galls as feeding sites for the parasites. Here we describe the role of local auxin synthesis induced during RKN infection. Exogenous application of auxin synthesis inhibitors decreased RKN gall formation rates, gall size and auxin response in galls, while auxin and auxin analogues produced the opposite effects, re-enforcing the notion that auxin positively regulates RKN gall formation. Among the auxin biosynthesis enzymes, YUCCA4 (YUC4) was found to be dramatically up-regulated during RKN infection, suggesting it may be a major contributor to the auxin accumulation during gall formation. However, yuc4-1 showed only very transient decrease in gall auxin levels and did not show significant changes in RKN infection rates, implying the loss of YUC4 is likely compensated by other auxin sources. Nevertheless, yuc4-1 plants produced significantly smaller galls with fewer mature females and egg masses, confirming that auxin synthesized by YUC4 is required for proper gall formation and RKN development within. Interestingly, YUC4 promoter was also activated during cyst nematode infection. These lines of evidence imply auxin biosynthesis from multiple sources, one of them being YUC4, is induced upon plant endoparasitic nematode invasion and likely contribute to their infections. The coordination of these different auxins adds another layer of complexity of hormonal regulations during plant parasitic nematode interaction.